Etiology of Carpal Tunnel Syndrome in a Large Cohort of Children - Christina T. Rüsch; Ursula Knirsch; Daniel M. Weber; Marianne Rohrbach; André Eichenberger; Jürg Lütschg; Kirsten Weber; Philip J. Broser; Georg M. Stettner (MDPI AG, 2021)
(1) Background: Carpal tunnel syndrome (CTS), a compressive mononeuropathy of the median nerve at the wrist, is rare in childhood and occurs most frequently due to secondary causes. (2) Methods: Medical history, electrodiagnostic findings, and imaging data of patients with CTS from two pediatric neuromuscular centers were analyzed retrospectively. The etiology of CTS was investigated and compared with the literature. (3) Results: We report on a cohort of 38 CTS patients (n = 22 females, n = 29 bilateral, mean age at diagnosis 9.8 years). Electrodiagnostic studies of all patients revealed slowing of the antidromic sensory or orthodromic mixed nerve conduction velocities across the carpal tunnel or lack of the sensory nerve action potential and/or prolonged distal motor latencies. Median nerve ultrasound was diagnostic for CTS and confirmed tumorous and vascular malformations. Etiology was secondary in most patients (n = 29; 76%), and mucopolysaccharidosis was the most frequent underlying condition (n = 14; 37%). Idiopathic CTS was rare in this pediatric cohort (n = 9; 24%). (4) Conclusion: Since CTS in childhood is predominantly caused by an underlying disorder, a thorough evaluation and search for a causative condition is recommended in this age group.